Clinical Biomarkers of Dyslipidemia in Diabetes Mellitus Type II Patients - Afzal , Ali; Kausar, Robina; Aslam, Sana; Shahid, Nayab; Aman, Suneela; Zohaib, Muhammad; Rehman, Amna; Afzal, Nimra; Abbasi, Mudassir Hassan; Sheikh, Nadeem; Khawar, Muhammad Babar (BioScientific Review, 2024)
Background. This study aims to comparatively investigate the clinical biomarkers of diabetic dyslipidemia in type II diabetes mellitus (TIIDM) patients and healthy controls with no clinical diabetic history. Method. A cross-sectional study was conducted on 100 TIIDM patients age-matched with 100 control subjects. They were evaluated from January 2021 to July 2022 in Narowal, Pakistan. Various biomarkers including total cholesterol (TL), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and triglycerides were measured for each subject. Results. The results showed significantly higher levels of TC (238 ± 30 mg/dl), triglycerides (201 ± 72 mg/dl), and LDL (141 ± 47 mg/dl) in TIIDM patients as compared to control groups’ levels of TC (167 ± 23 mg/dl), triglycerides (175 ± 75 mg/dl), and LDL (95 ± 30 mg/dl). However, HDL level was significantly lower (46 ± 21 mg/dl) in TIIDM patients as compared to control group (54 ± 27 mg/dl). Conclusion. The clinical biomarkers of dyslipidemia are effective risk predictors for cardiovascular diseases in low-income countries such as Pakistan.